Winternals defragmentation, recovery, and administration field guide - Kleiman, Dave (Syngress Pub., 2006)
Provides information on Winternals tools that are used in many Microsoft networks worldwide. This book begins with a chapter describing the common challenges faced by system administrators related to system recovery, data backup and system performance enhancements. It also introduces a suite of Winternals solutions, including Recovery Manager.